2 - Le développement et l'agriculture en Algérie depuis l'indépendance - AHMED, Abdelkader SID (Africa Development, 1981)
The purpose of this article is to study the impact of the Algerian experience of development on its agriculture since independence . With the advantage of a growing petrol income , Algeria has chosen to build a self - centered economy based on a highly capitalistic type of industry. In the minds of Algerian policy makers , the development of the industrial sec- tor and particularly the development of intermediate and capital goods industries (especially fertilizers and agricultural equipment) was to provide the means for changing and modernizing the agrarian sector. This objective met with a number of obstacles : First the concentration of human and financial investments in the industrial sector located in the already favoured areas of the country deprived the rural sector of the very means for that development. Secondly the high cost of the import-substitution products and the substantial amounts drawn by the public import mono- polies have encumbured the budgets of agricultural entreprises. Thirdly the inedequacy of the commercial lines originally intended to fight against speculation by private agents together with the deterioration of the terms of trade of agricultural products discouraged agricultural production itself. Finally , the prolonged decrease of incomes from agriculture in sharp contrast to the increasing urban and industrial incomes (partly due to petrol ), provoked a huge rural depopulation which resulted in an accelerated depletion of labour supply in agriculture. These factors , amongst other , explain the rather poor results in Algerian agriculture since independence the consequence of which is the increasing inflation of agricultural and food imports. This is a serious problem for the Algerian authorities whose basic objective still is the building of a self-centered national economy. Abdelkader SID AHMED